EFFECTIVENESS OF HYDROXYAPATITE ON BONE RENOVATION - Jubaedah, Siti; Sudarkirana, Sultan Nuur; Citraresmi , Siti Annisa; Pakpahan, Evie Lamtiur (Moestopo International Review on Social, Humanities, and Sciences, 2025)
Tissue damage caused by trauma, fracture or disease requires restoration to restore its function to its original state. According to data from the Hospital Information System (SIRS) 2010, cases of bone fractures in Indonesia have increased every year. Bone healing requires cells to form new bone. Hydroxyapatite (HA) is a ceramic biomaterial that is widely used because it has chemical and structural characteristics similar to the inorganic components of bones and teeth, its osteoconductivity/inductivity is very good, biocompatible and does not cause an inflammatory response. The main source of HA is synthetic materials that are chemically and biologically natural (eggshells and cuttlefish, coral, natural calcite and cow bones). In previous studies, eggshells have a higher ability in bone formation. To explain the effectiveness of hydroxyapatite in bone remodeling. Analyzing journals sourced from the PubMed, Ebsco, Google Scholar data bases taken from 2012 to 2024. There are 15 references that have been found and cover the topic of the effectiveness of hydroxyapatite on bone remodeling. Conclusion: Hydroxyapatite is effective in bone remodeling because it has a main mineral composition that resembles the mineral composition of bones, has biocompatible properties and does not cause an inflammatory response.